Tinjauan Perlindungan Hukum Terhadap Konsumen Dalam Perjanjian Kontrak Bisnis - Rafi, Muhammad; Dzaky Naufal Tsany; Rido Yosep Angelio s; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
: Legal protection for consumers in business contracts in Indonesia is increasingly important issues along with economic development and the complexity of transactions that occur. This study aims to explore and analyze the existing legal framework, especially Law No. 8 of 1999 concerning Consumer Protection, and the challenges faced in its implementation. The method used is a normative legal approach with qualitative analysis of various legal sources and related literature. The results of the study indicate that although the law provides a strong legal basis for protecting consumers, there are still a number of obstacles in practice. Among them are the lack of consumer understanding of their rights, weak law enforcement, and the dominant bargaining position of business actors which often harms consumers. In addition, the development of technology and electronic transactions adds to the complexity of this problem, where existing regulations have not fully accommodated the need for consumer protection in the digital era.